2016
DOI: 10.1371/journal.pone.0155220
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 Enhances Migration and Resistance against Cisplatin in Endometrial Carcinoma Cells

Abstract: PurposeLipocalin 2 (LCN2) is a secretory protein that is involved in various physiological processes including iron transport. We previously identified LCN2 as an up-regulated gene in endometrial carcinoma, and found that the overexpression of LCN2 and its receptor, SLC22A17, was associated with a poor prognosis. However, the functions and mechanism of action of LCN2 currently remain unclear.MethodsThe LCN2-overexpressing endometrial carcinoma cell lines, HHUA and RL95-2, and LCN2-low-expressing one, HEC1B, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Moreover, as mentioned earlier, p53 was found to be downregulated in NGAL knockdown cells. Our results were similar to previous studies where NGAL was shown to regulate the expression of p53 [45,46]. and decreases autophagy.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, as mentioned earlier, p53 was found to be downregulated in NGAL knockdown cells. Our results were similar to previous studies where NGAL was shown to regulate the expression of p53 [45,46]. and decreases autophagy.…”
Section: Discussionsupporting
confidence: 93%
“…LCN2, also known as oncogene 24p3 or neutrophil gelatinase-associated lipocalin (NGAL), belongs to the lipocalin family. Recently, LCN2 was reported to potentially play important roles in tumour progression and chemoresistance in many kinds of cancer 17 . Hence, we selected LCN2 for further analysis.…”
Section: Lcn2 Was Up-regulated After Cisplatin Treatment and Down-regmentioning
confidence: 99%
“…Chemotherapy sensitivity may be due to changes in gene expression caused by epigenetic changes such as DNA methylation at the promoter after treatment 18 . Methylation at promoters has been reported to play an important role in regulating LCN2 expression 17 . So we evaluated methylation status after vitamin D and cisplatin treatment.…”
Section: Lcn2 Was Up-regulated After Cisplatin Treatment and Down-regmentioning
confidence: 99%
“…Although it is now well-established that LCN2 has fundamental modulator activities during hepatic insult, there is still some work that remains to be done prior announcing LCN2 as a therapeutic target. Currently, initial studies that use anti-LCN2 antibodies (Tarín et al, 2016 ), siRNAs or shRNAs targeting LCN2 (Volpe et al, 2013 ; Miyamoto et al, 2016 ), specialized nanoparticle-based theranostic agents (Guo et al, 2016 ), or modulators that impacts LCN2 receptor expression (Cui et al, 2008 ) in different settings are initiated. In addition, the design of therapeutic small-molecule inhibitors for LCN2 was recently proposed (Suk, 2016 ).…”
Section: Lcn2 In Therapymentioning
confidence: 99%